A Meta-Analysis on Computer Technology Intervention Effects on Mathematics Achievement for Low-Performing Students in K-12 Classrooms. (March 2021) - Ran, Hua; Kasli, Murat; Secada, Walter G.
This meta-analysis extended the current literature regarding the effects of computer technology (CT) on mathematics achievement, with a particular focus on low-performing students. A total of 45 independent effect sizes extracted from 31 empirical studies based on a total of 2, 044 low-performing students in K-12 classrooms were included in this meta-analysis. Consistent with previous reviews, this study suggested a statistically significant and positive effect of CT (d ¯  = 0.56) on low-performing students' mathematics achievement. Of four CT types, the largest CT effect was found with problem-solving system (d ¯  = 0.86), followed by tutoring( d ¯  = 0.80), game-based intervention (d ¯  = .58), and computerized practice (d ¯  = .23). Furthermore, other moderators were found to explain variation in CT effects on low-performing students' mathematics achievement. Study findings contributed to clarifying the effect of CT for low-performing students' mathematics achievement. Implications for instructional design and practices are also discussed.